2007
DOI: 10.1111/j.1600-0854.2007.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Dysferlin in Membrane Trafficking and Patch Repair

Abstract: The muscular dystrophies are a heterogeneous group of inherited disorders, defined by progressive muscle weakness and atrophy. Following the discovery of dystrophin, remarkable progress has been made in defining the molecular properties of proteins involved in the various dystrophies. This has underlined the importance of the dystrophin‐associated protein complex as a cell membrane scaffold, providing structural stability to muscle cells (McNeil PL, Khakee R. Disruptions of muscle fiber plasma membranes. Role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
108
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 77 publications
4
108
0
7
Order By: Relevance
“…3,4 However, dysferlin is also expressed in many other cell types, including CD14 ϩ monocytes. 5,6 Thus, nonmyofiber cells may possibly contribute to the disease process.…”
mentioning
confidence: 99%
“…3,4 However, dysferlin is also expressed in many other cell types, including CD14 ϩ monocytes. 5,6 Thus, nonmyofiber cells may possibly contribute to the disease process.…”
mentioning
confidence: 99%
“…In a direct role dysferlin might allow a wounded cell to survive an injury. It has been proposed that Ca 2+ influx through a plasma membrane breach triggers dysferlin-mediated membrane fusion to seal the lesion (Bansal et al, 2003;Glover and Brown, 2007;Lennon et al, 2003;McNeil and Kirchhausen, 2005). Alternatively, an indirect role for dysferlin in wound repair may involve intercellular signaling (Chiu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery, dysferlin has been referred to as a plasma membrane protein that is also found in cytoplasmic vesicles (Anderson et al 1999;Bansal et al 2003), largely because it appears enriched at the sarcolemma in cross sections of snap-frozen, unfixed muscle. The accumulation of subsarcolemmal vesicles in dysferlinopathic muscle, and studies of muscle fibers cultured from mice lacking dysferlin that involve laser wounding or other damaging treatments, have suggested that dysferlin's function is to repair disrupted plasma membranes (Bansal and Campbell, 2004;Glover and Brown, 2007;Han and Campbell, 2007).…”
mentioning
confidence: 99%